Analisis Pengaruh Getaran Peledakan Terhadap Kestabilan Lereng Pada Tambang Batubara Pit Roto Selatan Site Kideco, Kecamatan Batu Sopang, Kabupaten Paser, Provinsi Kalimantan Timur - Mukhammad Sofyan Rizka A; Fahrudin Fahrudin; Narulita Santi (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2017)
In PT. BUMA site, there are some landslide which affected by blasting activity. Blasting activity iscarried out to destroy overburden material. The purpose of this research is to know the type oflandslide, the coefficient value of vibration decay from Peak Particle Acceleration (PPA), rock masscondition constant value from Peak Particle Acceleration (PPA), the Peak Particle Acceleration (PPA)value and the maximum acceleration (amax) which is at a point of safe in South Roto Pit. The researchmethods which used are the window mapping method in several sections at South Roto Pit.Description of rock mass that includes type of rock, rock strength, degree of weathering, block shape,type and shape of discontinuity, discontinuity filler and roughness level of discontinuity. ThisDescription of rock mass use Geological Strength Index (GSI) classification as a parameter to knowthe mechanical properties of rock mass (cohesion and internal shear angle). The research area has atype of toppling failure with eastward avalanche. The value of coefficient of vibration decay from PPA(k) is 44,66. The rock mass condition constant (α) is 1,802. The safe value of PPA highwall slopesarea of B STA 1 value is 0,184 g and the maximum acceleration (amax) value is 0,12 g. Highwall slopesarea B STA 2 with PPA value is 0,0769 g and maximum acceleration (amax) value is 0,05 g. Highwallslopes area C5 STA 3 with PPA value is 0,153 g and the maximum acceleration (amax) value is 0,1 g.Highwall slopes area C5 STA 4 with PPA value is 0,0307 g and the maximum acceleration (amax) valueis 0,02 g. Overall slopes area with PPA value is 0,0307 g and maximum acceleration (amax) value is0,02 g.